Functional Outcome of Non-Operatively Treated Displaced Mid-shaft Clavicle Fractures in Adult - Khadka, S; Upreti, Suresh; Bhandari, PS (Nepal Orthopaedic Association Journal, 2021)
Background: Clavicle fractures are common injuries in young, active individuals, especially those who participate in sports where high-speed falls or violent collisions are frequent. There is increasing trend towards operative treatment closed midshaft clavicle fracture but it needs a cautious case selection. Study aim was to analyze the short term functional outcome of non-operatively managed displaced mid-shaft clavicle fracture. Method: In this prospective observational study, 33 consecutive patient with displaced mid-shaft clavicle fractures treated non-operatively in the Orthopedics Department at the Tribhuvan University teaching hospital were followed up to three months. All the patient after the diagnosis of the injury, received clavicle brace and arm pouch sling as non-operative management. Functional outcome assessment was done using the Constant score. Result: The mean age of the patient in our study was 32.42 +/- 7.83 years. Clavicle fracture predominant involved male gender (78.8% male Vs 21.2% female), left side was involved more commonly than right (63.6% Left Vs 36.4% Right) and the most common mode of injury was Road traffic accident (RTA 66.7%, Fall 27.3% and sports 6%). The mean clavicle shortening was 0.723+/- 0.52 cm. The mean constant score at final assessment 89.67/100. We observed significant correlation between clavicle fracture shortening and constant score at 3 months (p < 0.001). Conclusion: Our study revealed that functional outcome of non-operative management of displaced mid shaft clavicle fracture have a significant correlation with the amount of shortening.